Simulasi dan Pembuatan Prototipe Generator Listrik Bertenaga Langkah Mekanis untuk Aplikasi Energi Terbarukan - Nur Afiqoh, Nabella Sofa; Trisnoaji, Yuki; Novena, Nindia Nova; Atha, Muh Farhan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The design and fabrication of a Mechanical Footstep Power Generator was developed as an innovative approach to harness kinetic energy from footsteps and convert it into electrical energy. Using a fabrication analysis and Design for Assembly (DFA) method, the prototype was designed to be both efficient and easy to assemble. The system consists of nine primary components, including the top plate, bottom plate, gear plate, gear, pinion, spring, dynamo (DC), long bolt M12, and nut. Fabricated parts were processed through tapping, drilling, milling, grinding, shaping, and chamfering, while other components were commercially purchased. DFA analysis indicated a medium level of assembly complexity, with potential errors mitigated by applying error proofing and systematic assembly guidelines. Experimental testing demonstrated a consistent increase in electrical output corresponding to the number of steps applied, starting from 2.96 V and 0.0074 W at the first step, reaching 5.71 V and 0.051961 W at the twentieth step. These results confirm that the prototype can reliably convert mechanical energy into electrical energy, though its application is currently limited to low-power usage. Nevertheless, the system presents significant potential for future development aimed at improving efficiency, capacity, and broader applicability in renewable energy solutions.